Imatinib reduces bone marrow fibrosis and overwhelms the adverse prognostic impact of reticulin formation in patients with chronic myeloid leukaemia - AYDİN, YILDIZ (BMJ PUBLISHING GROUP, 2016)
Aims Before the era of tyrosine kinase inhibitors (TKIs), the presence of bone marrow fibrosis (MF) in patients with chronic myeloid leukaemia (CML) has been established as a poor prognostic factor. The aim of the present study was to evaluate the effects of imatinib treatment on MF and the prognostic significance of MF at this new era of CML therapy. Methods The study cohort consisted of 135 patients with CML who were exposed to imatinib. The grades of MF pre and post imatinib together with cytogenetic and molecular responses were evaluated. Results Severe MF (grade II-III) was observed in 44 (33%) patients prior to imatinib therapy, and in 8 (8%) after 12months of imatinib treatment (p=0.001). The complete cytogenetic response (CCyR) rates at 12months did not differ according to the pre-imatinib MF grades, and CCyR rates in patients with grades 0, I, II and III MF were 36/47 (76.5%), 26/33 (78.7%), 12/23 (52.1%) and 7/10 (70%), respectively (p=0.127). There was no significant difference between patients with or without CCyR at 12months of imatinib regarding grades of MF (p=0.785). The distribution of the major molecular response rates at 18months according to pre-treatment grades of MF were determined as grade 0 in 38/45 (84.4%), grade I in 21/28 (75%), grade II in 14/21 (66.6%) and grade III in 7/10 (70%) (p=0.112). There was no significant difference in overall survival rates between initial MF mild (grade 0-I) and severe (grade II-III) groups (p=0.278). Conclusions According to our findings, MF regresses with imatinib therapy over time, and the MF grades at diagnosis do not have a negative impact on the responses to imatinib treatment. Therefore, the adverse prognostic impact of the MF among patients with CML seems to disappear in the era of the TKIs.
Keywords: CML; MYELOFIBROS; HEMATOPATHOLOGY; CHRONIC MYELOGENOUS LEUKEMIA; KINASE INHIBITOR STI571; CHRONIC-PHASE; RELEVANCE; THERAPY; RECOMMENDATIONS; DIAGNOSIS